COVID-19 pandemic: Is there any impact on the mental health of athletes? - Rayinda Faizah; Hermahayu (UIR Press, 2022)
The COVID-19 Pandemic has led to the emergence of restrictive polices that have an impact not only on the physical aspect but also on the psychological impact of athletes. This study aims to examine the mental health conditions of Central Java athletes. The research method used is descriptive qualitative which is conducted on 20 athletes in Central Java. The sampling technique in this research is purposive sampling technique. This research is conducted in five stages, namely the preparation of definitions, observation-interview guidelines, data collection, data analysis, and data interpretation. Methods of data collection using observation and interview techniques. The collected data is then analyzed through data verification, coding, tabulation, and presentation. The results of this study indicate that the COVID-19 pandemic has an impact on aspects of activity related to sport activities, aspects of mental condition, and aspects of financial well being of athletes. In the aspect of mental state, the athletes showed some negative emotion such as boredom, disapppoitment, and confusion. The emergence of these negative emotions resulted in decreased concentration and decreased motivation of the athletes in training. Mental problem that do not get psychological treatment are feared to be the cause of the emergence of disorders more severe mental health in athletes. The results of this study can be used as recommendations for coaches and the government in developing programs to improve athlete achievement through physical and mental strengthening. Suggestions for further research are the need to develop an instrument for measuring athletes' mental health and analyzing mental health factors in athletes during a pandemic.